Curie depth and heat flow analysis of Ikot Ekpene and environs, Eastern Niger Delta Basin, using airborne magnetic data - Iduma, Uche; Stephen Onyejiuwaka, Stephen; Charity Nkiru, Nwokeabia (International Journal of Advanced Geosciences, 2020)
Aeromagnetic dataset over Ikot Ekpene and environs, Eastern Niger Delta Basin, was processed to compute the basement depth, Curie isotherm depth, geothermal gradient and heat flow within the area in order to investigate the depth to magnetic sources, geothermal prospect and the hydrocarbon potential of the place. The adopted computational method transformed the spatial data into frequency domain and provided a relationship between radially average power spectrum of the magnetic anomalies and the depths to respective sources.Â The results of the analysis showed that the depths to centroids and top boundaries range from 7.84 to 13.38 km and 0.233 to 0.459 km respectively. Curie depths within the basin undulate and vary between 15.42 and 26.49 km. The geothermal gradients range between 20.758 and 35.649 â°C/km while the corresponding heat flow is about 51.896 mWmâ»Â² within east of Ikono, north of Mbak and west of Abak Areas and 89.124 mWmâ»Â² within Amawum, Ndoro, Isiala, Ogbuebule and east of Uyo Areas. Based on the computed sedimentary thicknesses, high geothermal gradients and delineated major faults and fractures which could serve as migratory pathway for hydrocarbon or hydrothermal fluid, some parts of the study area have been demarcated for geothermal prospect and detail hydrocarbon exploration.Â Â